Kombucha from Edible Plants as a Functional Beverage with Hypoglycemic Potential: A Review - Nadya Treesna Wulansari; Ni Wayan Kesari Dharmapatni; Ida Ayu Manik Damayanti (Jurnal Pijar MIPA, 2026)
Diabetes mellitus (DM) is an endocrine disorder caused by a deficiency or ineffective production of insulin by the pancreas, leading to abnormal blood glucose levels. Hypoglycemia is a significant complication of diabetes therapy, referring to the condition or mechanisms that lower blood glucose levels. Kombucha is a functional beverage known for its health benefits, particularly its potential to reduce blood glucose levels. The data collection strategy used in this review was a systematic review.  Ten articles were used in this systematic review. Several plants, including sappan wood, Rhizophora mucronata leaves, snake fruit, Cyperus rotundus L. rhizomes, black tea, green tea, Solanum betaceum Cav., strawberry, Syzygium polyanthum (Wight) Walp. leaves, and red ginger, have demonstrated potential hypoglycemic effects. The mechanisms involved include inhibition of α-glucosidase enzyme activity, reduction of fasting plasma glucose (FPG), and decreased blood glucose concentration. The presence of secondary metabolites in these plants, combined with the fermentation process involving microorganisms, contributes to their antidiabetic potential through hypoglycemic mechanisms and α-glucosidase inhibition.